Retrospective analysis of the effect of SGLT-2 inhibitors on renal function in patients with type 2 diabetes in the real world - Song, Rongjing; Hou, Qiaoyu; Zhang, Xiuying; Zhao, Wei; Liu, Gang; Li, Meng; Zhang, Xiaohong; Ji, Linong (Frontiers in Pharmacology, 2024)
Introduction The protective effect of sodium–glucose cotransporter-2 (SGLT-2) inhibitors on the kidneys has been widely recognized. However, limited research has reported the changes in estimated glomerular filtration rate (eGFR) of real-world patients with type 2 diabetes mellitus (T2DM) over time after administration of SGLT-2 inhibitors. This study aimed to reflect the trend of eGFR changes over time in T2DM patients having different baseline eGFR after SGLT-2 inhibitors administration in the real world. Methods A single-center retrospective study was performed in a tertiary public hospital in Beijing, China. In total, 998 outpatients with T2DM who initiated SGLT-2 inhibitors treatment were included in the study. The changes in eGFR, urinary albumin/creatinine ratio (UACR), and glycolipid metabolism indicators were analyzed during the 18-month follow-up period. Results The eGFR levels significantly decreased to their lowest point (−3.04 mL/min/1.73 m2) in the first 3 months after initiation of SGLT-2 inhibitors treatment, however, gradually returned to the baseline level after 1 year. Compared to the subgroup with eGFR >90 mL/min/1.73 m2, improvements in renal function were more significant in patients with T2DM from the 60 < eGFR ≤90 mL/min/1.73 m2 and eGFR ≤60 mL/min/1.73 m2 subgroups after treatment with SGLT-2 inhibitors. Similarly, SGLT-2 inhibitors reduced the UACR in patients with diabetic nephropathy. Conclusion This study further confirmed the real-world long-term protective effect of SGLT-2 inhibitors on the kidneys of patients with T2DM, which is not related to baseline renal function and blood glucose.